2012
DOI: 10.1089/dna.2012.1706
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Insertion/Deletion Polymorphism in the Proximal Promoter ofCD3GIs Associated with Susceptibility for Hepatocellular Carcinoma in Chinese Population

Abstract: Hepatocellular carcinoma (HCC) represents the most common primary malignancy of the liver with a worldwide increasing incidence. Although the risk factors for HCC are well characterized, the molecular mechanisms responsible for malignant transformation of hepatocytes are not well understood. In this study, a case-control study including 291 HCC patients and 294 healthy controls was conducted to investigate the association between HCC susceptibility and with a 4-bp insertion/deletion polymorphism (rs66465034) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Studies have found that genetic defects of CD3G can lead to impaired expression of CD3 and TCR on the cell surface, so CD3G mutations are related to immune function defects [ 38 ]. CD3G gene polymorphism may affect the occurrence of liver cancer [ 39 ]. At present, most of the research on CD3G focuses on tumors, and there are few reports on vascular diseases and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that genetic defects of CD3G can lead to impaired expression of CD3 and TCR on the cell surface, so CD3G mutations are related to immune function defects [ 38 ]. CD3G gene polymorphism may affect the occurrence of liver cancer [ 39 ]. At present, most of the research on CD3G focuses on tumors, and there are few reports on vascular diseases and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that genetic defects of CD3G can lead to impaired expression of CD3 and TCR on the cell surface, so CD3G mutations are related to immune function defects [32] . CD3G gene polymorphism may affect the occurrence of liver cancer [33] . At present, most of the research on CD3G focuses on tumors, and there are few reports on vascular diseases and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that genetic defects of CD3G can lead to impaired expression of CD3 and TCR on the cell surface, so CD3G mutations are related to immune function defects [38] . CD3G gene polymorphism may affect the occurrence of liver cancer [39] . At present, most of the research on CD3G focuses on tumors, and there are few reports on vascular diseases and thrombosis.…”
Section: Discussionmentioning
confidence: 99%